Insights on the Effects of Heat Pretreatment, pH, and Calcium Salts on Isolation of Rare Actinobacteria from Karstic Caves - Fang, Bao-Zhu; Salam, Nimaichand; Han, Ming-Xian; Jiao, Jian-Yu; Cheng, Juan; Wei, Da-Qiao; Xiao, Min; Li, Wen-Jun (Frontiers in Microbiology, 2017)
The phylum Actinobacteria is one of the most ubiquitously present bacterial lineages on Earth. In the present study, we try to explore the diversity of cultivable rare Actinobacteria in Sigangli cave, Yunnan, China by utilizing a combination of different sample pretreatments and under different culture conditions. Pretreating the samples under different conditions of heat, setting the isolation condition at different pHs, and supplementation of media with different calcium salts were found to be effective for isolation of diverse rare Actinobacteria. During our study, a total of 204 isolates affiliated to 30 genera of phylum Actinobacteria were cultured. Besides the dominant Streptomyces, rare Actinobacteria of the genera Actinocorallia, Actinomadura, Agromyces, Alloactinosynnema, Amycolatopsis, Beutenbergia, Cellulosimicrobium, Gordonia, Isoptericola, Jiangella, Knoellia, Kocuria, Krasilnikoviella, Kribbella, Microbacterium, Micromonospora, Mumia, Mycobacterim, Nocardia, Nocardioides, Nocardiopsis, Nonomuraea, Oerskovia, Pseudokineococcus, Pseudonocardia, Rhodococcus, Saccharothrix, Streptosporangium and Tsukamurella were isolated from these cave samples.